The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2023
DOI: 10.3390/jimaging9090190
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Extraction of Deep Image Features Using a Convolutional Neural Network (CNN) for Detecting Ventricular Fibrillation and Tachycardia

Azeddine Mjahad,
Mohamed Saban,
Hossein Azarmdel
et al.

Abstract: To safely select the proper therapy for ventricular fibrillation (VF), it is essential to distinguish it correctly from ventricular tachycardia (VT) and other rhythms. Provided that the required therapy is not the same, an erroneous detection might lead to serious injuries to the patient or even cause ventricular fibrillation (VF). The primary innovation of this study lies in employing a CNN to create new features. These features exhibit the capacity and precision to detect and classify cardiac arrhythmias, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 74 publications
(91 reference statements)
0
2
0
Order By: Relevance
“…When comparing our proposed model with state-of-the-art models validated in the same public dataset, it is important to note that few CNN studies have reported using single lead to identify multiple types of arrhythmias, regardless of whether they utilized open datasets. However, there are some similar experiments, such as those focusing on using single-lead ECG to detect AFIB [ 27 ] and using CNN to detect VT and VF [ 28 ]. Yun et al utilized 11 open-source databases from PhysioNet and developed a deep learning model based on transformer for AFIB/AFL segmentation in single lead ECG using self-supervised learning with masked signal modeling [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When comparing our proposed model with state-of-the-art models validated in the same public dataset, it is important to note that few CNN studies have reported using single lead to identify multiple types of arrhythmias, regardless of whether they utilized open datasets. However, there are some similar experiments, such as those focusing on using single-lead ECG to detect AFIB [ 27 ] and using CNN to detect VT and VF [ 28 ]. Yun et al utilized 11 open-source databases from PhysioNet and developed a deep learning model based on transformer for AFIB/AFL segmentation in single lead ECG using self-supervised learning with masked signal modeling [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…A. Mjahad et al . used MIT-BIH and AHA databases and employed four different CNN architectures (InceptionV3, MobileNet, VGGNet, and AlexNet) to discern VF and VT features [ 28 ]. The results showed a sensitivity of 98.16% and specificity of 99.07% for VF, sensitivity of 90.45% and specificity of 99.73% for VT, sensitivity of 99.34% and specificity of 98.35% for NSR, and sensitivity of 96.98% and specificity of 99.68% for other rhythms, with corresponding accuracies.…”
Section: Discussionmentioning
confidence: 99%